2013
DOI: 10.1097/mpg.0b013e318267c320
|View full text |Cite
|
Sign up to set email alerts
|

Antireflux Surgery in Children With Neurological Impairment

Abstract: Serious complications were uncommon in this series of antireflux surgery in neurologically impaired children. Although gagging and retching were common following surgery, a high percentage of caregivers reported improved nutrition, reflux-related symptoms, and high levels of satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
29
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 37 publications
4
29
0
1
Order By: Relevance
“…The high rate of complications in children with neurological impairment after fundoplication cannot be explained by the surgical technique (12,22). Extreme rumination, retching and gagging can increase the complication rate due to increased intra-abdominal pressure (12) and may be responsible for a higher rate of repeat fundoplication in children with neurological deficiencies (26,27). Gastric emptying is not negatively affected by a semipartial fundoplication in children with neurological deficiencies (23).…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of complications in children with neurological impairment after fundoplication cannot be explained by the surgical technique (12,22). Extreme rumination, retching and gagging can increase the complication rate due to increased intra-abdominal pressure (12) and may be responsible for a higher rate of repeat fundoplication in children with neurological deficiencies (26,27). Gastric emptying is not negatively affected by a semipartial fundoplication in children with neurological deficiencies (23).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports suggest that the effect of ARS is doubtful because of significant complications and the high GER recurrence rate [12,16,17]. However, O'Loughlin et al [5] reported that fundoplication in NI patients indicated high levels of caregiver satisfaction with the results of the surgical intervention. Moreover, Mauritz et al [4] showed in their systematic review that the success rate of ARS in NI patients may not be inferior to that of normally developed children.…”
Section: Discussionmentioning
confidence: 97%
“…Acid suppression therapy is one of the effective treatments for esophagitis; however, it is often difficult to control other GERD symptoms, such as malnutrition or pulmonary aspiration, in NI patients suffering from abnormal body posture, scoliosis, and convulsion. When medical treatments fail and reflux symptoms persist, antireflux surgery (ARS) is often required to prevent refluxassociated morbidity such as recurrent aspiration [4,5]. Several ARS procedures can be used for gastro-esophageal reflux (GER) treatment, with surgical fundoplication, where the gastric fundus is wrapped around the distal esophagus, being the most common.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, failure of open or laparoscopic fundoplication (LapFundo) has been consistently shown to be more likely in those with ND compared to neurologically normal children: while reported rates of failure depend on definitions used and duration of follow-up, large contemporary series of LapFundo report a requirement for re-do surgery in 6%-14% at 20-36 months [11][12][13][14][15]. Other problems with fundoplication in ND include high rates of dysphagia, gagging and retching, as well as dumping syndrome and gas bloating postsurgery [14,16].…”
mentioning
confidence: 96%